A GARCH approach to modeling Chilean long-term swap yields - Tanweer Akram; Khawaja Mamun (Levy Economics Institute of Bard College, 2022)
This paper econometrically models the dynamics of the Chilean interbank swap yields based on macroeconomic factors. It examines whether the month-over-month change in the short-term interest rate has a decisive influence on the long-term swap yield after controlling for other factors, such as the change in inflation, change in the growth of industrial production, change in the log of the equity price index, and change in the log of the exchange rate. It applies the generalized autoregressive conditional heteroskedasticity (GARCH) approach to model the dynamics of the long-term swap yield. The change in the short-term interest rate has an economically meaningful and statistically significant effect on the change of the interbank swap yield. This means that the Banco Central de Chile's (BCCH) monetary policy exerts an important influence on interbank swap yields in Chile.
Keywords: E43; E50; E58; E60; G10; G12; 330; Interest Rate Swaps; Swap Yield; Short-Term Interest Rate; Banco Central de Chile (BCCH); Chile